(untitled) (Phenomenology, Humanities and Sciences, 2023)
Despite the fallacious discourse of racial democracy, the racism present in Brazil harms thousands of people daily. Nevertheless, the study of whiteness as the white racial identity that is related to a privileged social position in front of persons classified as non-white is still initial in the phenomenology field. Thereby, the present study intended to think about this matter and utilized a film of a great national audience, “The Second Mother”(2015), as research data. A film analysis with a phenomenological approach was performed on behalf of the whiteness aspects present in Brazilian cinema, and the following meaning units were found and analyzed: white superiority, encounter with the rationalized woman, and white fragility. The film context in which the interactions occur within an employer-domestic worker relationship brings specific features to the whiteness livingness and makes the racism situations invisibilized.